A study of neuronal ceroid lipofuscinosis proteins CLN5 and CLN8 - De Silva, Weerakonda Arachchige Bhagya Nilukshi (Kansas State University, 2015)
Neuronal ceroid lipofuscinoses (NCLs) are a group of neurodegenerative lysosomal storage disorders which is the most frequent group of inherited neurodegenerative disorders that affect children leading to severe pathological conditions such as progressive loss of motor neuron functions, loss of vision, mental retardation, epilepsy, ataxia and atrophy in cerebral, cerebella cortex and retina and eventually premature death. Among the many genes that cause NCL, mutations in CLN5 leads to different forms of NCL (infantile, late infantile, juvenile and adult) and mutations in CLN8 leads to progressive epilepsy with mental retardation (EPMR) and a variant late infantile form of NCL. The function(s) of both CLN5 and CLN8 proteins remain elusive. CLN5 is a glycosylated soluble protein that resides in the lysosome. We observed that endogenous CLN5 protein exist in two forms and identified a previously unknown C-terminal proteolytic processing event of CLN5. Using a cycloheximide chase experiment we demonstrated that the proteolytic processing of CLN5 is a post-translational modification. Furthermore treatment with chloroquine showed the processing occurs in low pH cellular compartments. After treatment with different protease inhibitors our results suggested the protease involved in the processing of CLN5 could be a cysteine protease. Using two glycosylation mutants of CLN5, retained in the endoplasmic reticulum (ER) or the Golgi we showed the proteolytic processing occurs in an organelle beyond the ER. This study contributes to understanding the characteristics of the CLN5 protein. CLN8 is an ER resident transmembrane protein that shuttles between the ER and the ER-Golgi intermediate compartment (ERGIC). In our study we identified a potential interaction between CLN8 and a PP2A holoenzyme complex consisting regulatory subunit A α isoform and regulatory subunit B α isoform. Using two CLN8 patient derived fibroblast cell lines we were able to show that the phosphorylated levels of PP2A target kinase Akt was reduced at both of its regulatory sites Ser473 and Thr308 and the activity of PP2A was increased. A delay of ceramide transport from ER to Golgi in CLN8 deficient patient cell lines was observed using BODIPY FL C5-Ceramide staining. Our results provide evidence for CLN8 protein being involved in the regulation of PP2A activity and trafficking of ceramide from ER to Golgi.
Keywords: Lysosomal storage disorder; Neuronal ceroid lipofuscinosis; CLN5; CLN8